Iron oxide nanoparticles as dielectric and piezoelectric enhancers for silicone elastomers. (21st September 2017) - Iacob, Mihail; Tugui, Codrin; Tiron, Vasile; Bele, Adrian; Vlad, Stelian; Vasiliu, Tudor; Cazacu, Maria; Vasiliu, Ana-Lavinia; Racles, Carmen
Abstract: Iron oxide nanoparticles were prepared using an alkaline precipitation method to tune the reaction time so as to afford ferrihydrite with spherical morphology or goethite nanorods. These two nanoparticle types, surface-treated with a surfactant (Pluronic L81), were each incorporated in 10, 20 and 30 wt% within a polydimethylsiloxane- α, ω -diol (Mn = 60 000 g mol −1 ). The mixtures were processed as films and crosslinked by condensation with tetraethoxysilane at room temperature. The aged films were investigated concerning filler distribution (by SEM coupled with an energy-dispersive x-ray spectroscopy module), mechanical (tensile strength, elongation and Young's modulus), and dielectric properties (permittivity, loss, conductivity and strength). The results show that the fillers have a relatively homogeneous distribution within the matrix and, dependent on the filler nature and amount, generally manifest a mechanical reinforcing effect and act as dielectric permittivity and strength enhancers. In addition, it has been found that the crystalline nanoparticles induce a piezoelectric response, emphasized by piezoelectric force microscopy. The improved properties of the composites make them suitable for applications in mechanical/electrical energy conversion, as theoretical estimates showed.